Severe Recurrent Fever Episodes With Clinical Diagnosis of Hemophagocytic Lymphohistiocytosis, Incomplete Kawasaki Disease and Systemic-Onset Juvenile Idiopathic Arthritis: A Case Report and Literature Review - Jiang, Hongkun; Yang, Zhiliang (Frontiers in Pediatrics, 2020)
The pathogeneses of recurrent fever are quite complicated when excluding repeated infections. Recurrent fever is a common symptom for autoinflammatory diseases, relapse of Systemic-onset juvenile idiopathic arthritis (SoJIA) and recurrent Kawasaki disease (KD). There are no specific diagnostic laboratory tests for the diseases. Some studies showed that KD was the precursor of hemophagocytic lymphohistiocytosis (HLH). Macrophage activation syndrome (MAS) is another form of HLH in SoJIA. Cytokine disturbances are considered to be involved in the pathogenesis of the diseases. We describe a Chinese female toddler that developed three separate fever episodes with eventual diagnose of SoJIA over about 10 months. The first episode was diagnosed as IKD, immunoglobulin nonresponsive KD, and HLH. The second and third episodes were diagnosed as IKD and SoJIA, respectively. The fever was hard to be relieved by antipyretics, and the peak axillary temperature was above 40°C. For every fever episode, infections were excluded. For the first episode, trends over time of hemoglobin, platelets, fibrinogen, and triglycerides indicated HLH, which was finally diagnosed and treated according to the HLH-2004 protocol. For the second episode six months later, after excluding an HLH relapse and infections, IKD was finally diagnosed. Oral aspirin was administered, and the HLH treatment was ceased. The third episode occurred three months later, and SoJIA was finally diagnosed. For each episode, except for relative tests, we only tested for cytokines interleukin-1β, interleukin-6, and interferon-γ, due to limited laboratory test availability. These cytokines were elevated during remission and rose much higher in the fever phases. The case showed the difficulty to differentiating the recurrent fever in clinical practice. Surveillance of routine laboratory parameters over time might reveal a trend that indicates possible disease, even when parameter values do not meet diagnostic criteria. Changes in cytokine profiles are promising markers for differentiating recurrent fever diseases in future. An unknown immunological defect for the case may contribute to the recurrent immunological insults, and we are following up the recurrence of fever episode.